A comparative analysis of conventional and modern methods of credit risk assessment in financial institutions: implications for micro, small and medium enterprises (MSMEs) - Hossain, Nabiha (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.